2022
DOI: 10.3892/br.2022.1513
|View full text |Cite
|
Sign up to set email alerts
|

Lotus essential oil improves neurite elongation and facilitates functional recovery after peripheral nerve injury

Abstract: Injury to the peripheral nerve may lead to deficits in nerve function. An increase in the levels of free radicals plays a role in inhibition of nerve regeneration following damage. The aim of this study was to investigate the effects of lotus essential oil (LEO) on neurite outgrowth in vitro and nerve regeneration in vivo in a rat model of sciatic nerve crush injury. Gas chromatography-mass spectrometry analysis showed that the principal constituent of LEO was palmitic acid ethyl ester (25.12%). The radical sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Additionally, nerve damage also causes sensory loss ( 3 ). Our results showed that PB treatments after injury to sciatic nerve could improve the number of DRG neurons in L4-L6 DRG and restore sensory function within 21 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, nerve damage also causes sensory loss ( 3 ). Our results showed that PB treatments after injury to sciatic nerve could improve the number of DRG neurons in L4-L6 DRG and restore sensory function within 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were randomly divided into 5 groups (control, sham, sciatic nerve crush (SNC), SNC + 20 mg/kg of PB, and SNC + 40 mg/kg of PB, n=6 in each group). The SNC injury was performed as described previously ( 3 ). Briefly, a single dose of 50 mg/kg sodium pentobarbital was injected intraperitoneal to anesthetize the rats.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation